2019
DOI: 10.1002/cbin.11220
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits myofibroblast formation via induction of apoptosis and antagonism of pro‐fibrotic gene expression in human dermal fibroblasts

Abstract: The anti-malaria drug artesunate and other chemical analogs of artemisinin have demonstrated cytostatic and cytotoxic effects in bacterial and cancer cells. Artemisinin-derived compounds have also been demonstrated to attenuate fibrosis in preclinical animal models, but the mechanisms by which this inhibition occurs are not well-understood. We investigated the effects of artesunate on the emergence of the myofibroblast, which is causally implicated in pro-fibrotic pathologies. CRL-2097 human dermal fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In burns, the prolonged inflammatory response over-activates myofibroblasts leading to overexpression of various components of the ECM and, therefore, the development of hypertrophic scars. Recent studies have targeted fibrosis by inducing myofibroblast apoptosis [143,144] including the use of gene therapy [144] and cuprous oxide nanoparticles [145].…”
Section: Myofibroblasts and Apoptosismentioning
confidence: 99%
“…In burns, the prolonged inflammatory response over-activates myofibroblasts leading to overexpression of various components of the ECM and, therefore, the development of hypertrophic scars. Recent studies have targeted fibrosis by inducing myofibroblast apoptosis [143,144] including the use of gene therapy [144] and cuprous oxide nanoparticles [145].…”
Section: Myofibroblasts and Apoptosismentioning
confidence: 99%
“…These effector molecules can be problematic during the "cytokine storm" suffered by many SARS-CoV-2 patients (Schett et al 2020). Artemisinin also blunts fibrosis (Larson et al 2019;Dolivo et al 2020), another problem experienced by SARS-CoV-2 survivors that causes more lasting damage to organs (Lechowicz et al 2020;Liu et al 2020a). A recent report showed that a number of artemisinin-related compounds have some anti-SARS-CoV-2 activity, with dihydroartemisinin, artesunate, and arteannuin B having IC50 values <30 µM (Cao et al 2020), and dihydroartemisinin ACTs having 1-10 µM IC50 values (Bae et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These effector molecules can be problematic during the “cytokine storm” suffered by many SARS-CoV-2 patients (Schett et al 2020). Artemisinin also blunts fibrosis (Larson et al 2019; Dolivo et al 2020), another problem experienced by SARS-CoV-2 survivors that causes more lasting damage to organs (Lechowicz et al 2020; Liu et al 2020a). A recent report showed that a number of artemisinin-related compounds have some anti-SARS-CoV-2 activity, with dihydroartemisinin, artesunate, and arteannuin B having IC 50 values <30 μM (Cao et al 2020), and dihydroartemisinin ACTs having 1-10 μM IC 50 values (Bae et al 2020).…”
Section: Introductionmentioning
confidence: 99%